Overexpression of two stress-responsive, small, non-coding RNAs, 6S and tmRNA, imparts butanol tolerance in Clostridium acetobutylicum. Issue 8 (16th March 2016) - Jones, Alexander J.; Venkataramanan, Keerthi P.; Papoutsakis, Terry
Abstract : While extensively studied in several model organisms, the role of small, non-coding RNAs in the stress response remains largely unexplored in Clostridium organisms. About 100 years after the first industrial Acetone–Butanol–Ethanol fermentation process, based on the Weizmann Clostridium acetobutylicum strain, strain tolerance to butanol remains a crucial factor limiting the economics of the process. Several studies have examined the response of this organism to metabolite stress, and several genes have been engaged to impart enhanced tolerance, but no sRNAs have yet been directly engaged in this task. We show that the two stress-responsive sRNAs, 6S and tmRNA, upon overexpression impart tolerance to butanol as assessed by viability assays under process-relevant conditions. 6S overexpression enhances cell densities as well as butanol titres. We discuss the likely mechanisms that these two sRNAs might engage in this tolerance phenotype. Our data support the continued exploration of sRNAs as a basis for engineering enhanced tolerance and enhanced solvent production, especially because sRNA-based strategies impose a minimal metabolic burden on the cells. Abstract : Among several identified stress-responsive sRNAs, 6S and tmRNA are shown to impart butanol tolerance to Clostridium acetobutylicum .. Abstract :